Conventional testing produces submaximal values for oxygen uptake in elite runners - Beltrami, F. G.; Noakes, T. D. (International Journal of Sports Physiology and Performance, 2021)
Purpose: This study aimecd to investigate whether elite athletes could reach higher values of maximal oxygen uptake (VO2max) during a decremental exercise test in comparison with a traditional incremental test, as recently demonstrated in trained individuals.